University students’ perception of whatsapp-based religious messages (2021)
WhatsApp has been widely used to disseminate religious information but there is scant literature on users’ reaction to religious messages on WhatsApp. This study therefore investigated how university students perceive WhatsApp-based religious messages (WBRM). The study was driven by the Uses and Gratifications theory and the Perception theory. It adopted a mixed- method research design to gather relevant data. Through stratification and purposive sampling techniques, 350 students of the University of Ibadan were selected to participate in the survey while 24 students were selected to participate in four different sessions of focus group discussion (FGD). Results showed that most of the students (71%) paid little or no attention to these messages as they did not feel comfortable with long, threatening, instructive religious messages. Nonetheless, findings implied that university students had a favourable disposition towards the use of WhatsApp for religious purpose s. A majority perceived the messages as educative, informative, persuasive and useful. The study also found that students’ perception of WhatsApp-based religious messages and benefits derived from WBRM have a strong positive and significant influence on each other. Producers of WhatsApp-based religious messages, targeting young people, should keep the messages short, ensure that the messages are authentic and avoid fear appeal